Efficient ultrasonic assisted adsorption of organic pollutants employing bimetallic-carbon nanocomposites. Issue 17 (22nd November 2021) - Saharan, Priya; Kumar, Vinit; Mittal, Jyoti; Sharma, Vishal; Sharma, Ashok K.
ABSTRACT: In recent times, carbon nanofibers (CNF) have been used extensively for the remediation of environment owing to their hollow layered organization, high specific surface area, and strong electrostatic interactions which formulate it as an appropriate adsorbent material. Metallic nanoparticles were blended onto its surface in order to engineer a novel metal-CNF nanocomposite. The study aimed the ultrasonic assisted adsorption of rhodamine B dye (RhB) and pesticide dichlorophenoxyacetic acid (2, 4-D) out of aqueous matrix by using silver (Ag) and copper (Cu) based bimetallic composite (Ag-Cu/CNF) material. The synthesized nanocomposites were characterized for its crystalline analysis, textural characteristics, surface chemical bonding, and specific surface area. Ag-Cu/CNF illustrated superior adsorptive efficiency when compared with Ag/CNF and Cu/CNF. Adsorption equilibrium was studied by Freundlich and Langmuir isotherms. Evaluation of the data predicted that Langmuir model described the maximum fit toward equilibrium data with utmost adsorption efficiency of 201 mg/g and 112 mg/g for RhB and 2, 4-D, respectively. Also, the comparison between adsorption aided by ultrasound, magnetic stirrer, and vortex shaker assisted methods revealed that sono-sorption is a proficient option for commencement of adsorption phenomenon due to convenient and facile diffusion. Graphical Abstract: